Consumers Networks and Search Equilibria - Andrea Galeotti (Tinbergen Institute, 2004)
I examine a search model a la' Burdett and Judd (1983). Consumers are embedded in a consumers network, they may costly search for price quotations and the information gathered are non-excludable along direct links. This allows me to explore the effect of endogenous consumers externalities on market functioning. I first show that when search costs are low consumers randomize between searching for one price and two price quotations (high intensity search equilibrium). Otherwise, consumers randomize between searching for one price and not searching at all (low intensity search equilibrium). Second, in both equilibria consumers search less frequently in denser networks. Finally, when search costs are low the expected price and the social welfare increase as the consumers network becomes denser. These results are reverse when search costs are high.
Keywords: C72; D83; 330; Networks; Consumers Externalities; Search; Konsumentenverhalten; Netzwerk; Informationskosten; Suchtheorie